Molecular identification and life cycle of Black Soldier fly (Hermetia illucens) in laboratory (Bangladesh Journal of Zoology, 2021)
Molecular identification and life cycle of the Black Soldier Fly (BSF), Hermetia illucens were carried out from the Bangladesh bio-geographical area. The sequencing result and phylogenetic analysis of BSF showed 99-100% similarity with H. illucens from GenBank. The average duration of life cycle of male and female were 45.08±4.46d and 46.15± 4.12d respectively. The adult female is 16.3±0.91mm long, whereas the adult male is 14.30±0.19 mm long and smaller than female. The number of eggs per clutch was 537.37±40.21 which hatched in 4.36±0.24 days. The mean duration of the developmental stages were 16.07±2.59, 15.4±2.50, 9.95±1.48 and 10.33±1.89 d for larva, pupa, male and female respectively, when cultured at 29.40±1.77° C, RH 68.25±2.32 %, 14:10 (L: D) photoperiod. The mature larval weight (0.20±0.03 g) was highest among other developmental stages.Bangladesh J. Zool. 48(2): 429-440, 2020